Best practices in the implementation of pandemic era learning in non-formal education institution - A. Adityo; S. Sudiran; Ayuningtyas Rachmayani; Darioush Sharafie (Universitas Muhammadiyah Malang, 2023)
During the COVID-19 pandemic, institutions were forced to shift their teaching from face-to-face classes to online classes. In non-formal education, this means that there are different styles and approaches to teaching that are being employed without proper training or guidance as they are not following the general curriculum provided by the government. The research intended to assist non-formal education by validating their teaching and learning process during the COVID-19 period. The study follows the ADDIE (Analyze, Design, Develop, Implement, and Evaluate) model to analyze and give an evaluation of the teaching practice. The research is a form of community service assistance in determining the best practices for teaching language during a pandemic in Mayantara School Malang. The result is proposed as a reference for other non-formal education. The research resulted in best practices in managerial and teaching applications. The result is divided into three principal best practices, teaching approaches, cooperation, and material development. The non-formal education should understand these aspects well and further implement their teaching and learning activities to prepare for situations that may occur.